Report of the seventh annual Trades' union congress : held at Liverpool, on January 18th, 19th, 20th, 21st, 22nd, and 23rd, 1875 - Trades union congress (07 ; 1875 ; Liverpool)
Published (by the authority of the Congress and the Parliamentary committee), by William Owen